Genetic variation and clonal propagation of superior genotypes of selected Acacia species - Muniandi, Sures Kumar (2015)
The Acacia species was introduced into Malaysia in the late 1960’s for timber production. Plantations of Acacia species gain interest as a major timber species in the 1960’s especially in Peninsular Malaysia along with Hevea brasiliensis. The product in forestry ventures is often sawn timber, which requires trees to be in good conditions such as straight, single-stemmed and defect-free trunks for maximum utilization. Production of such quality wood is another big problem in forestry plantation since trees grown in plantation of some high-value temperate and tropical hardwood species tend to produce low value, short butt logs and bolts due to crooked stems, low fork heights and delayed shedding of lower branches. In this context, a research study was initiated to select and recommend the best performing tree species or provenances suited for timber production in Malaysia with respect to growth and other characteristics. Species/provenance/progeny test was conducted on four species of Acacia namely, A.mangium, A.auriculiformis, A.crassicarpa and A. aulococarpa with four provenances for each species from two main regions of Papua New Guinea and Queensland. The growth of the provenances was monitored in terms of some quantitative and qualitative characteristics to evaluate the genetic variation and growth performance of a base breeding population. The study showed that there were significant differences (p< 0.05) between species, provenance and progenies for their growth performance. There were also significant differences between provenances within regions and progenies within provenances in all quantitative and qualitative traits tested in this study. Generally, with regard to the growth, A.mangium performs better compared to other Acacia species in all of the aspects tested and it was followed by A.crassicarpa, A.aulococarpa and A.auriculiformis. Generally provenances and progenies selected from Papua New Guinea excelled those from Queensland both in quantitative and qualitative characteristics. Among the top performing progenies of Acacia species are CG 1854 of (Bensbach WP) and KN000107 (SW of Boset WP) of A.mangium, BVG2609 (Bensbach WP) of A.crassicarpa, BVG 00835 (WP Morehead) and MM1016 (Arufi E Morehead WP) of A.aulococarpa and JSL363 (Wenlock River) and BVG 2657 (Bansbach) of A.auriculiformis. Three best performing clone (genotypes) were then chosen based on their phenotypic characteristic for clonal propagation of superior tree species through traditional and modern techniques. Vegetative propagation was attempted as initial pretreatment stage of rejuvenation of mature sources through forced flushing, stem cuttings and trunk decapitation. A. mangium and A. auriculiformis respond well to force flushing by having highest survival percentage (87.7% and 90%, respectively) together with bud breaking and sprout growth. Whereas, A.aulococarpa and A.crassicarpa only recorded 52.2% and 31.1% of survival percentage. Rooting ability of stem cuttings, feasible and mean root number and root length increase at juvenile stage for all species studied. Rooting ability of mature cuttings decreased and bud breaks occurred only for few days eventually died, and did not respond to the treatments of growth regulators. Rooting ability of young stem cuttings of A. mangium (83.3%) and A.auriculiformis (76.6%) was better compared to that of A.crassicarpa and A aulococarpa with only 48% and 68.8%, respectively. Investigation was also done for the use of coppice materials as an alternative source for in vitro propagation of mature sources. 12 yearold trees of selected Acacia species were felled to the height of 1.0m and 1.5m. Vigorous production of sprout or coppice was noted on the stumps of trees of all species except of A.crassicarpa. The greatest copping ability in terms of survival rate of stumps was observed on A.auriculiformis with 83.8% followed by, A.mangium, A.aulococarpa and A.crassicarpa with 75.0%, 40.0% and 1.67 %, respectively. A.crassicarpa produces a very low number of sprouts with mean of 0.03 and mean of 0.09 for sprout length. Rejuvenated mature explants were further subjected to in vitro conditions for mass production of improved materials for establishment of efficient in vitro protocol for Acacia sp. Decontamination of field collected materials was conducted as an initial stage in shoot initiation stage using some methods optimized in preliminary study. Most effective sterilization in term of average clean culture percentage (>70%) was recorded in 0.1% HgCl2 for 5 minutes for A.mangium, A.auriculiformis, A.mangium ‘Superbulk’ and A. hybrid and 0.1% HgCl2 for 10 minutes for both A.crassicarpa and A.aulococarpa. Incorporation of 0.1g/l of fungicide Benomyl with 50mg/ml of antibiotic streptomycin further enhanced the survival rate and percentage of clean culture up to 80%-100%. Multiple shoot production was obtained from all species of Acacia on Murashige and Skoog (MS) medium supplemented with 2.0 mg/l benzyladenine (BA) plus 0.5 mg/l of NAA. It was also noted that greater shoot production occurred with combination of plant growth regulators with additives. The maximum shoot number and shoot length was produced in medium supplemented with 2.0 mgl-1 benzyladenine (BA) + 0.5 mgl-1 of NAA + activated charcoal (0.1% w/v) combined with 100 mgl-1 AdSO4. It produced maximum number of 9.0 shoots per explant with 3.51 cm in length. Shoots were then elongated and rooted in an optimized condition and further acclimatized to nursery condition.Another study was initiated to evaluate and identify sequence markers which gave phylogenetic information to be used to infer relationship within Acacias at a fine level. Primer designed based on second intron of LEAFY gene of A.mangium amplified the specific region with single band except for A. hybrid. The amplified regions were sequenced to reveal the species relationship within selected Acacias. Result revealed that non coding region of the second intron of LEAFY gene is more variable and can be used as marker for phylogenetic studies at lower taxanomic levels.